HEROISM IN LIN CARTER’S NOVEL THE QUEST OF KADJI - Sawira Sawira; Jumino Suhadi; M. Manugeren (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2017)
Abstract The focus of the study goes to the protagonist’s heroism in making his country a peaceful state. There always seems to be a hero in everyone’s life; everyone has one, and many act as one. A. hero is simply a man admired for his achievements and noble qualities. Despite the accuracy of any dictionary, a hero can be defined according to the mind of the beholder. Heroes have been constructed in many fictional literary works and myths, as well as in reality.  This research is conducted by means of descriptive qualitative method proposed by Krathwohl (2010), and the theory of heroism applied is the one proposed by Kohen (2010). There are three forms of heroism showed by Kadji, the protagonist of the novel: courage, sacrifice and suffering. Kadji is still young but urged by his courage, he is ready to take an official assignment to finish the enemy of his state, named Shamad. The study is conducted by applying descriptive qualitative method with purposes of describing, explaining and validating things related to the data taken from the novel. From the research result it is seen that Kadji in quest of the enemy experiences sacrifice and suffering but motored by his courage all is settled down  to the upmost outcome. Kadji is a real patriot for his state and his clans as he has shown a spirit of heroism in all his steps. Kadji has proved himself to be a hero. It is in line with what Kohen (2010) claims that  heroes are people who transform compassion or a personal virtue into heroic action or a civic virtue. He has proved so much to his forefathers of his fatherland that they do not tolerate traitors.  Keywords: heroism, courage, sacrifice, suffering